2018
DOI: 10.20964/2018.01.19
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran as Source for the Synthesis of Imidazoline-type Inhibitors: Synthesis and Corrosion Performance

Abstract: Based on its high oil content, this research proposes the use of an agro-industrial by-product (rice bran) as a sustainable option for the synthesis of environmentally friendly corrosion inhibitors. The extraction and characterization of the raw rice bran oil was carried out, and the imidazoline-type inhibitors were synthesized from a 1:3 molar ratio (oil:aminoethylethanolamine). The corrosion inhibitory capacity of the product obtained was evaluated by electrochemical techniques such as potentiodynamic polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Thus, the goal of this research work is to evaluate the use of a gemini surfactant imidazoline kind obtained from mango seed as a green inhibitor for the CO 2 corrosion of X-120 steel. In addition to this, and by comparing with previously published results [35][36][37][38], to try to find a correlation between the alkyl chain length, the presence of double bond of the hydrophobic chain of imidazoline and its inhibition performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the goal of this research work is to evaluate the use of a gemini surfactant imidazoline kind obtained from mango seed as a green inhibitor for the CO 2 corrosion of X-120 steel. In addition to this, and by comparing with previously published results [35][36][37][38], to try to find a correlation between the alkyl chain length, the presence of double bond of the hydrophobic chain of imidazoline and its inhibition performance.…”
Section: Introductionmentioning
confidence: 99%
“…Different organic compounds such as amides, amines or imidazolines have been extracted from different agro-industrial wastes such as coffee bagasse, coconut, avocado and rice brain and used as corrosion inhibitors for steel in acidic environments including CO 2 [ 35 , 36 , 37 , 38 ]. Mexico is the fifth-largest mango producer in the world, with a volume of 1.88 million tons with an annual growth rate of 3.8%.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds can form protective layers on the metal surface, either by absorption or precipitation. Most corrosion inhibitors are organic compounds, and in their structure, they contain nitrogen (N), sulfur (S), and oxygen (O) atoms, unsaturated functional groups, as well as aromatic rings that favor their adsorption on the metal surface, due to a lone pair of electrons [6][7][8][9][10][11]. Corrosion inhibitors can reduce metal dissolution by at least 90% when they are added to the electrolyte in doses as low as ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, because it has been observed that the amide and imidazoline inhibitors derived from fatty acids reach their maximum surface coverage between 4 and 12 h after their addition, depending on the origin of the fatty acids, type of fatty acids, and proportion of fatty acids [ 5 , 8 , 23 , 25 , 49 ], once the optimal dose of inhibition was determined, potentiodynamic polarization curves were performed, at different immersion times of the working electrode, at a scan rate of 1 mV/s from −400 mV to +600 mV with respect to the corrosion potential. Each polarization curve was obtained with new working electrodes at different immersion times (0, 1, 3, 6, 9, 12, 18, and 24 h).…”
Section: Methodsmentioning
confidence: 99%
“…Amide- and imidazoline-type compounds of fatty acids of vegetable origin (ampholytic compounds) have been found to be excellent corrosion inhibitors because in their structure they have nitrogenous groups and aliphatic chains that act as a metallophilic and hydrophobic group, respectively [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. It has been recognized that the most efficient inhibitors are those with aliphatic chains with 16–18 carbon atoms [ 9 ], and since in vegetable oils the largest proportion of their fatty acids correspond precisely to those with 18C chains, it is for this reason that they are used for the synthesis of corrosion inhibitors and the high inhibition efficiencies obtained.…”
Section: Introductionmentioning
confidence: 99%